2017
DOI: 10.1186/s12884-017-1407-4
|View full text |Cite
|
Sign up to set email alerts
|

The third delay: understanding waiting time for obstetric referrals at a large regional hospital in Ghana

Abstract: BackgroundDelay in receiving care significantly contributes to maternal morbidity and mortality. Much has been studied about reducing delays prior to arrival to referral facilities, but the delays incurred upon arrival to the hospital have not been described in many low- and middle-income countries.MethodsWe report on the obstetric referral process at Ridge Regional Hospital, Accra, Ghana, the largest referral hospital in the Ghana Health System. This study uses data from a prospectively-collected cohort of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 11 publications
5
79
0
Order By: Relevance
“…Waiting times from labour ward arrival to initial assessment also improved. Prior to the triage training, the median (IQR) patient waiting time from arrival to initial assessment was 40 (15-100) min, with a maximum wait time of 1 day 2.5 hrs (Goodman et al,2017). Following training, a review of 203 admissions between December 15-31, 2014 found that waiting times were reduced to 29 (11-60) min (p=0.007), which achieved the institutional goal of 30 min.…”
Section: Waiting Timesmentioning
confidence: 99%
See 2 more Smart Citations
“…Waiting times from labour ward arrival to initial assessment also improved. Prior to the triage training, the median (IQR) patient waiting time from arrival to initial assessment was 40 (15-100) min, with a maximum wait time of 1 day 2.5 hrs (Goodman et al,2017). Following training, a review of 203 admissions between December 15-31, 2014 found that waiting times were reduced to 29 (11-60) min (p=0.007), which achieved the institutional goal of 30 min.…”
Section: Waiting Timesmentioning
confidence: 99%
“…Data was collected from December 15 th -31 st , 2014 to determine the length of time women waited from arrival to initial assessment. This was compared to the baseline established in 2012 as reported by Goodman, et al, (2017).…”
Section: Stage 4 -Evaluation Of Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…49 In addition, over and above the delays before making the decision to refer, and in reach-ing the referral site, factors associated with a ''third delay", those incurred after arrival at the hospital, have been identified in a low middle-income country. 50 In response, a novel obstetric triage system has been introduced, successfully reducing the delay from arrival at the referral centre to the first assessment by a midwife. 51,52 Strategies to identify critically ill patients, enable early and appropriate management and thus prevent avoidable critical care admissions, are paramount.…”
Section: Challenges To the Provision Of Maternal Critical Care In Resmentioning
confidence: 99%
“…4,16 Transportation is a challenge to women especially in rural settings where there are little or no means of transportation or access to health facilities where basic obstetric care could be given;hence, patients with ruptured uterus may end up losing both their babies and their lives. 3,4,18 Ruptured uterus may continue to be a common cause for maternal and perinatal mortality for sometime to comeif we standby and do nothing.…”
Section: -4mentioning
confidence: 99%